A method for preparing a film-coated workpiece and its application

By using oil removal agents and modified wetting liquids of organic weak acids, acid salts, water softeners and zwitterionic surfactants, combined with PVD activation steps, the surface flatness and storage problems in the plastic plating process are solved, and the coating is realized. Stability and environmentally friendly process flow.

CN115928003BActive Publication Date: 2025-02-11深圳市生利科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210491724.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-07
Publication Date
2025-02-11
Estimated Expiration
2042-05-07

AI Technical Summary

Technical Problem

In the existing plastic electroplating process, there are still major problems with the flatness and storage properties of the surface layer, and the use of acidic oil removal methods containing chromium compounds will cause pollution to the environment.

Method used

Use oil removal agents that work together with weak organic acids, acid salts, water softeners and zwitterionic surfactants to remove oil and impurities on the surface of plastic workpieces, avoid water washing and chromium-containing contamination, and pass the modified wetting liquid and PVD activation steps. Improve the hydrophilicity of the workpiece surface and the stability of the coating.

Benefits of technology

It realizes that there is no need for water washing after removing oil, avoids environmental pollution, and the coating is more stable, can be preserved for a long time in an environment with high humidity, maintaining moderate roughness on the surface of the workpiece, and improving the adhesion and overall performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003631316940000061
    Figure BDA0003631316940000061
  • Figure BDA0003631316940000062
    Figure BDA0003631316940000062
  • Figure BDA0003631316940000072
    Figure BDA0003631316940000072
Patent Text Reader

Abstract

The present invention relates to a preparation method and application of a coated workpiece. The steps are as follows: (1) degreasing; (2) roughening; (3) water washing; (4) PVD pretreatment; (5) PVD activation; (6) chemical plating. The use of organic weak acid, acid salt, water softener and zwitterionic surfactant together not only eliminates the need for water washing after degreasing, but also does not introduce chromium-containing compounds to pollute the environment, and does not generate a large number of bubbles during degreasing, which is conducive to more complete roughening, and makes the final coating more stable, and can be stored for a long time even in a high humidity environment; the active groups generated during the PVD activation process can synergize with the coating metal to improve the adhesion of the coating metal. The coated workpiece obtained by the preparation method provided by the present invention has low wastewater discharge generated by the entire process while improving the stability and mechanical properties of the workpiece coating, and is environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to C25D5, and more specifically, to a method for preparing a film-coated workpiece and application thereof. Background Art

[0002] Plastic electroplating products not only maintain the rigidity and processability of plastics, but also have the decorative and conductive properties of metals, and are widely studied. With the development of modern science, people have put forward more requirements for plastic electroplating products, which has brought great challenges to the plastic electroplating products industry.

[0003] Patent No. CN100455703C provides a plastic electroplating chromic anhydride-sulfuric acid type roughening process, which realizes the recovery of chromic anhydride used in the process, so that it can be recycled, thereby reducing pollution. Patent No. CN101701348B provides a roughening solution for pre-plating treatment of semiconductor N\P type cooling wafer surface and related pre-plating treatment process. The roughening solution formed by hydrofluoric acid, nitric acid and oxidant is used to treat the wafer, combined with sandblasting nickel plating, to improve the factory qualified rate of products.

[0004] Although people have reduced the environmental pollution of plastic electroplating process by improving the raw materials of plating liquid, there are still big problems with the surface smoothness and storage performance of many plastic products obtained by the improved process. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present invention provides a method for preparing a coated workpiece, the steps of which are as follows: (1) degreasing; (2) roughening; (3) water washing; (4) PVD pretreatment; (5) PVD activation; and (6) chemical plating.

[0006] As a preferred technical solution of the present invention, the degreasing is achieved by immersing the plastic workpiece in a degreasing agent.

[0007] Preferably, the plastic workpiece is made of ABS (acrylonitrile-butadiene-styrene) resin as a base material.

[0008] Preferably, the temperature during degreasing is 40-45° C. and the degreasing time is 2-4 min.

[0009] As a preferred technical solution of the present invention, the degreasing agent is a water-diluted mixed solution containing 7-8.5 wt % of an acidic degreasing agent.

[0010] Preferably, the acidic degreasing agent is selected from one or more of oxalic acid, acetic acid, glyoxylic acid, calcium bicarbonate, trisodium phosphate, sodium citrate, and N,N,N-trimethylglycine.

[0011] The CAS number of N,N,N-trimethylglycine is 107-43-7.

[0012] More preferably, the acidic degreasing agent is a mixture of oxalic acid, acetic acid, calcium bicarbonate, trisodium phosphate and N,N,N-trimethylglycine, wherein the weight ratio of oxalic acid, acetic acid, calcium bicarbonate, trisodium phosphate and N,N,N-trimethylglycine is (8-15): (3-6): (2-7): (0.4-1.5): (1-4).

[0013] Degreasing is mainly to remove oil and other impurities on the surface of plastic workpieces, so that the subsequent roughening is more uniform and the coating bonding is stronger. At present, alkaline degreasing or acidic degreasing is generally used, wherein alkaline degreasing generally uses sodium hydroxide, sodium carbonate, etc., while acidic degreasing generally uses chromate. Since the environment required for roughening is mostly an acidic environment, if alkaline degreasing is used, a large amount of water must be used to wash the workpiece after degreasing; if acidic degreasing is used, although it can be done without water washing, it will cause great pollution to the environment due to the use of chromium-containing compounds. In order to overcome the above problems, the applicant has found through a large number of experiments that the use of specific organic weak acids, acid salts, water softeners and zwitterionic surfactants can not only overcome the above problems, but also do not require water washing after degreasing, and will not introduce chromium-containing compounds to pollute the environment, and will not generate a large number of bubbles during degreasing, which is conducive to more complete roughening, and makes the final coating more stable, and can be stored for a long time even in a high humidity environment. This may be because, in the degreasing agent provided by the present invention, oxalic acid and acetic acid are used as organic weak acids, calcium bicarbonate is used as an acid salt, trisodium phosphate is used as a water softener, and N,N,N-trimethylglycine is used as a zwitterionic surfactant. The zwitterionic surfactant can synergize with the acid salt to give the plastic workpiece, especially the ABS plastic workpiece surface, a higher hydrophilicity. At the same time, the acid salt and the organic weak acid work together to significantly improve the ability of the degreasing agent to remove oil and other impurities on the surface of the ABS plastic workpiece, and further improve the tension of the workpiece surface and improve the stability of the coating. However, due to the addition of the acid salt, a trace amount of calcium ion-containing film will be formed on the plastic surface, thereby having a negative effect on the binding force of the coating, so that the binding force of the coating is reduced. For this reason, the applicant has found that the addition of a specific water softener can improve the negative effects caused by the addition of the acid salt, so that the calcium ions are precipitated through complexation. In addition, the applicant has unexpectedly found that in such a system with the addition of a specific water softener, the degreasing operation can be carried out smoothly and effectively at a temperature of 40-45°C, without the need to reach the traditional 60-75°C, which further saves costs.

[0014] As a preferred technical solution of the present invention, the roughening is specifically to immerse the plastic workpiece obtained after degreasing in step (1) in a roughening liquid for 15-30 minutes to obtain the workpiece 2.

[0015] Preferably, the roughening liquid is selected from one or more of a 40-70wt% aqueous solution of hydrochloric acid, a 25-60wt% aqueous solution of nitric acid, a 16-45wt% aqueous solution of potassium permanganate, and sodium lauryl sulfonate.

[0016] More preferably, the roughening liquid is a mixture of a 40-70wt% aqueous solution of hydrochloric acid, a 25-60wt% aqueous solution of nitric acid, a 16-45wt% aqueous solution of potassium permanganate, and sodium lauryl sulfonate. In the roughening liquid, the weight ratio of the 40-70wt% aqueous solution of hydrochloric acid, the 25-60wt% aqueous solution of nitric acid, the 16-45wt% aqueous solution of potassium permanganate, and sodium lauryl sulfonate is 1:(0.3-0.8):(0.1-0.25):(0.1-0.3).

[0017] Preferably, the roughening temperature is 20-26°C.

[0018] Preferably, the step (3) is specifically to rinse the workpiece 2 with 0.3-1.5 L of distilled water to obtain the workpiece 3.

[0019] As a preferred technical solution of the present invention, the step (4) is specifically to immerse the workpiece 3 in the modified impregnation liquid for 20-40 seconds, take it out, and vacuum dry it at 60°C for 40-50 minutes to obtain the workpiece 4. The modified impregnation liquid is homemade. The preparation method is as follows: propionic acid alcohol, vinyl trimethoxysilane and anhydrous aluminum chloride are mixed in a weight ratio of 0.7:0.4:0.1, added to tetrahydrofuran, and reacted at 70°C for 1.5-1.8 hours to obtain the modified impregnation liquid.

[0020] As a preferred technical solution of the present invention, the step (5) specifically includes placing the workpiece 4 in a vacuum coating machine for oxygen plasma glow treatment, setting the voltage of the vacuum coating machine to 100-200V, and the treatment time to 5-7min, so that active groups are generated on the surface of the workpiece 4 to obtain the workpiece 5.

[0021] The working principle of the vacuum coating machine is to use physical vapor deposition (PVD) technology to perform surface treatment to deposit a material layer on the surface of the substrate.

[0022] As a preferred technical solution of the present invention, the step (6) specifically comprises treating with a chemical nickel plating solution, rinsing, and drying to obtain a coated workpiece.

[0023] Preferably, the preparation method of the chemical nickel plating solution is: adding ammonia water and 6-8 wt % of dilute sulfuric acid aqueous solution into the plating solution, and adjusting the pH to 4.8-5.3.

[0024] Further preferably, the step (6) is specifically that the workpiece 5 is treated with a chemical nickel plating solution, then rinsed with distilled water, and vacuum dried at 60° C. for 4-6 hours to obtain a coated workpiece.

[0025] As a preferred technical solution of the present invention, the treatment time of the chemical nickel plating solution is 5-20 minutes.

[0026] Preferably, the chemical nickel plating solution treatment condition is a constant temperature water bath of 65-75°C.

[0027] A second aspect of the present invention provides an application of a method for preparing a coated workpiece, wherein the method for preparing a coated workpiece is applied to the aerospace industry, the automobile industry, the electronic computer industry and the mechanical industry.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The use of organic weak acid, acid salt, water softener and zwitterionic surfactant together not only eliminates the need for water washing after degreasing, and does not introduce chromium-containing compounds to pollute the environment, but also does not generate a large number of bubbles during degreasing, which is conducive to more complete roughening, and makes the final coating more stable, and can be stored for a long time even in an environment with high humidity; the roughening liquid prepared by mixing a 40-70wt% hydrochloric acid aqueous solution, a 25-60wt% nitric acid aqueous solution, a 16-45wt% potassium permanganate aqueous solution and sodium lauryl sulfonate in a weight ratio of 1: (0.3-0.8): (0.1-0.25): (0.1-0.3) can achieve good coordination with the modified impregnation liquid of the degreasing and subsequent PVD activation steps of the present invention, not only maintaining a moderate roughness of the workpiece surface, which is neither too smooth nor excessively corroded, but also further improving the hydrophilicity and wettability of the workpiece surface, which is conducive to forming a smooth and complete coating. The active groups generated during the PVD activation process can synergize with the plated metal to improve the adhesion of the plated metal. The plated workpiece obtained by the preparation method provided by the present invention has improved stability and mechanical properties of the workpiece coating, and the wastewater discharge generated by the entire process is low, which is environmentally friendly. DETAILED DESCRIPTION

[0030] Example

[0031] The raw materials for preparing the composition in the embodiment are all commercially available, among which the plastic workpiece is purchased from Xingteng, and the solid plate with a specification of 50mm×50mm×10mm is prepared with ABS resin as the substrate, vinyltrimethoxysilane is purchased from Xuanhao, model KH-171, the plating solution is purchased from Bigley, model PL-7, and the ammonia water is industrial ammonia water purchased from Jingke, item number 02030005.

[0032] Example 1

[0033] This example provides a method for preparing a coated workpiece, the steps of which are as follows: (1) degreasing; (2) roughening; (3) water washing; (4) PVD pretreatment; (5) PVD activation; and (6) chemical plating.

[0034] Degreasing was achieved by immersing the plastic workpiece in 100 mL of degreasing agent. The temperature during degreasing was 43°C and the degreasing time was 3 minutes.

[0035] The degreasing agent is a water-diluted mixture of 7.5 wt % acidic degreasing agent.

[0036] The acidic degreasing agent is a mixture of oxalic acid, acetic acid, calcium bicarbonate, trisodium phosphate and N,N,N-trimethylglycine, wherein the weight ratio of oxalic acid, acetic acid, calcium bicarbonate, trisodium phosphate and N,N,N-trimethylglycine is 12:5.2:3:0.8:1.5.

[0037] The roughening process is as follows: the plastic workpiece obtained after degreasing in step (1) is immersed in 100 mL of roughening liquid for 23 minutes to obtain workpiece 2.

[0038] The roughening liquid is a mixture of a 55wt% hydrochloric acid aqueous solution, a 40wt% nitric acid aqueous solution, a 20wt% potassium permanganate aqueous solution, and sodium lauryl sulfonate. In the roughening liquid, the weight ratio of the 55wt% hydrochloric acid aqueous solution, the 40wt% nitric acid aqueous solution, the 20wt% potassium permanganate aqueous solution, and the sodium lauryl sulfonate is 1:0.55:0.17:0.2.

[0039] The roughening temperature was 24°C.

[0040] The step (3) specifically comprises rinsing the workpiece 2 with 0.8 L of distilled water to obtain the workpiece 3.

[0041] Step (4) specifically comprises immersing the workpiece 3 in 100 mL of the modified impregnation liquid for 35 seconds, taking it out, and vacuum drying it at 60° C. for 45 minutes to obtain the workpiece 4. The modified impregnation liquid is homemade. The preparation method is as follows: propionic acid alcohol, vinyl trimethoxysilane and anhydrous aluminum chloride are mixed according to a weight ratio of 0.7:0.4:0.1 to 2.5 g, added to 50 mL of tetrahydrofuran, and reacted at 70° C. for 1.7 hours to obtain the modified impregnation liquid.

[0042] Step (5) specifically includes placing the workpiece 4 in a vacuum coating machine for oxygen plasma glow treatment, setting the voltage of the vacuum coating machine to 150 V, and the treatment time to 6 minutes, to obtain the workpiece 5.

[0043] The step (6) is specifically to wash the workpiece 5 with 500 mL of distilled water after the workpiece 5 is treated with the chemical nickel plating solution, and then vacuum dry it at 60° C. for 5 hours to obtain a coated workpiece. The preparation method of the chemical nickel plating solution is: add ammonia water and 6.5 wt% dilute sulfuric acid aqueous solution to the plating solution and adjust the pH to 5.1.

[0044] The treatment time of chemical nickel plating solution is 17 minutes.

[0045] The treatment condition of the chemical nickel plating solution is a constant temperature water bath at 72°C.

[0046] Example 2

[0047] This example provides a method for preparing a coated workpiece. The difference from Example 1 is that the weight ratio of oxalic acid, acetic acid, calcium bicarbonate, trisodium phosphate and N,N,N-trimethylglycine is 9:4:2.2:0.5:1.2. The roughening liquid is a mixture of an aqueous solution of 45wt% hydrochloric acid, an aqueous solution of 30wt% nitric acid, an aqueous solution of 18wt% potassium permanganate, and sodium lauryl sulfonate. In the roughening liquid, the weight ratio of the aqueous solution of 45wt% hydrochloric acid, the aqueous solution of 30wt% nitric acid, the aqueous solution of 18wt% potassium permanganate, and sodium lauryl sulfonate is 1:0.6:0.2:0.2.

[0048] Example 3

[0049] This example provides a method for preparing a coated workpiece. The difference from Example 1 is that the weight ratio of oxalic acid, acetic acid, calcium bicarbonate, trisodium phosphate and N,N,N-trimethylglycine is 13:5.5:4.3:1.2:1.6. The roughening liquid is a mixture of an aqueous solution of 60wt% hydrochloric acid, an aqueous solution of 55wt% nitric acid, an aqueous solution of 25wt% potassium permanganate and sodium lauryl sulfonate. In the roughening liquid, the weight ratio of the aqueous solution of 60wt% hydrochloric acid, the aqueous solution of 55wt% nitric acid, the aqueous solution of 25wt% potassium permanganate and sodium lauryl sulfonate is 1:0.7:0.14:0.15.

[0050] Example 4

[0051] This example provides a method for preparing a coated workpiece. The difference from Example 1 is that the weight ratio of oxalic acid, acetic acid, calcium bicarbonate, trisodium phosphate and N,N,N-trimethylglycine is 9:5:3:0.1:1.

[0052] Example 5

[0053] This example provides a method for preparing a coated workpiece. The difference from Example 1 is that the roughening solution is a mixture of a 60wt% hydrochloric acid aqueous solution, a 30wt% nitric acid aqueous solution, a 10wt% potassium permanganate aqueous solution, and sodium lauryl sulfonate. In the roughening solution, the weight ratio of the 60wt% hydrochloric acid aqueous solution, the 30wt% nitric acid aqueous solution, the 10wt% potassium permanganate aqueous solution, and the sodium lauryl sulfonate is 1:0.4:0.4:0.2.

[0054] Performance Test:

[0055] 1. Flatness test: Observe the appearance of the coated workpieces obtained in Examples 1-5. The results are shown in Table 1:

[0056] Table 1

[0057]

[0058] 2. Stability test: The coated workpieces obtained in Examples 1-5 were placed in an environment at 20°C and 70% humidity. After 20 days, the coating was observed to see if there was any fading, peeling or cracking. The results are shown in Table 2:

[0059] Table 2

[0060]

[0061]

[0062] 3. Peeling force test: The coated workpieces obtained in Examples 1-5 were subjected to peeling force test according to the tear (peel) strength standard of metal-plated plastics of ASTM B533-2004. The results are shown in Table 3:

[0063] Table 3

[0064]

Claims

1. A method for preparing a film-coated workpiece, characterized in that: The steps are as follows: (1) degreasing of plastic workpieces; (2) roughening; (3) water washing; (4) PVD pretreatment; (5) PVD activation; (6) chemical plating; The degreasing is achieved by immersing the plastic workpiece in a degreasing agent; the degreasing agent is a water-diluted mixed solution of 7-8.5wt% of an acidic degreasing agent; the acidic degreasing agent is a mixture of oxalic acid, acetic acid, calcium bicarbonate, trisodium phosphate and N,N,N-trimethylglycine; wherein the weight ratio of oxalic acid, acetic acid, calcium bicarbonate, trisodium phosphate and N,N,N-trimethylglycine is (8-15):(3-6):(2-7):(0.4-1.5):(1-4); The roughening is specifically performed by immersing the plastic workpiece obtained after degreasing in step (1) in a roughening liquid for 15-30 minutes to obtain workpiece 2; The roughening liquid is a mixture of a 40-70wt% aqueous solution of hydrochloric acid, a 25-60wt% aqueous solution of nitric acid, a 16-45wt% aqueous solution of potassium permanganate, and sodium lauryl sulfonate; in the roughening liquid, the weight ratio of the 40-70wt% aqueous solution of hydrochloric acid, the 25-60wt% aqueous solution of nitric acid, the 16-45wt% aqueous solution of potassium permanganate, and sodium lauryl sulfonate is 1: (0.3-0.8): (0.1-0.25): (0.1-0.3); The step (5) specifically includes placing the workpiece in a vacuum coating machine for oxygen plasma glow treatment.

2. The method for preparing a film-coated workpiece according to claim 1, characterized in that: The step (3) specifically comprises: washing the workpiece 2 with 0.3-1.5 L of distilled water to obtain the workpiece 3.

3. The method for preparing a film-coated workpiece according to claim 2, characterized in that: The step (4) specifically comprises immersing the workpiece 3 in the modified impregnation liquid for 20-40 seconds, taking it out, and vacuum drying it at 60° C. for 40-50 minutes to obtain the workpiece 4; the preparation method of the modified impregnation liquid is as follows: propionic acid alcohol, vinyl trimethoxysilane and anhydrous aluminum chloride are mixed in a weight ratio of 0.7:0.4:0.1, added to tetrahydrofuran, and reacted at 70° C. for 1.5-1.8 hours to obtain the modified impregnation liquid.

4. The method for preparing a coated workpiece according to any one of claims 1 to 3, characterized in that: The step (6) specifically comprises treating with a chemical nickel plating solution, rinsing, and drying to obtain a coated workpiece.

5. The method for preparing a film-coated workpiece according to claim 4, characterized in that: The chemical nickel plating solution treatment time is 5-20 minutes.

6. An application of the method for preparing a coated workpiece according to any one of claims 1 to 5, characterized in that: The method for preparing the coated workpiece is applied to the aerospace industry, the automobile industry, the electronic computer industry and the mechanical industry.

Citation Information

Patent Citations

  • Sulfuric acid type crude chemical technology of electroplating chromic anhydride on plastic

    CN100455703C

  • Coarsening solution for electroplating pretreatment on surface of semiconductor N\P type cooling wafer and related electroplating pretreatment process

    CN101701348B

  • Palladium-free activation process for plastic substrate surface of nickel adsorbed sodium carboxymethylcellulose by chelating function

    CN101381865A

  • Method for in-situ catalytic chemical plating of plasma modified polyimide film

    CN113652675A